Penguatan Lembaga Komisi Pemberantasan Korupsi Dalam Melakukan Penydidikan Menurut Undang-Undang Nomor 19 Tahun 2019 - Ramadona, Bintang (Lex Librum : Jurnal Ilmu Hukum, 2022)
Indonesia and at the same time as an attempt to encourage the Anti-Corruption Commission to fight corruption crimes. In the case of money laundering, there is a special link between organized crime and legal markets related to the art trade, the financial sector, and real estate. When it comes to corruption, there is a difference between corruption at the political, law enforcement, or administrative level. Van Dijk found a strong link between levels of corruption and organised crime around the world, as by Transparency International.But ties with illegal organizations are just one aspect of corruption. It is important to talk about corruption as a crime phenomenon because there are additional aspects associated with it. As mentioned earlier, criminologists place corruption in the category of organized crime. In the case of corporate crime, a company can act as an agent offering bribery in order to a company's objectives, such as obtaining a project or a government license. On the other hand, in the context of a crime in a company, members of a private organization or a public service will receive bribe for their own benefit, in exchange for services that may not be provided by an organization authorized by the Anti-Corruption Commission to commit a violation.